Proceedings of the COGENT regional coconut genebank planning workshop, 26-28 February 1996, Pekanbaru, Riau, Indonesia - Ramanatha Rao, V.; Batugal, P.; International Plant Genetic Resources Institute (1998)
To develop the draft work plans, agreements and funding strategies, this Regional Coconut Genebank Workshop was conducted in Riau, Pekanbaru, Indonesia near the site of one of the ICGs, from 26 to 28 February 1996. Under the Convention on Biological Diversity (CBD), countries are to exchange and use as well as to conserve their biodiversity. Accordingly, draft agreements including Material Transfer Agreements (MTAs) and Germplasm Acquisition Agreements (GAAs) were discussed and refined during the workshop. These model agreements lay out the terms and conditions under which countries are to provide the germplasm to the ICG, for users to make requests for germplasm and conditions under which the germplasm is to be transferred to the user. Although field genebanks in each hosting country will be the primary mechanism for conservation, other conservation methods, including in vitro and cryoconservation, may be developed once necessary technologies and funding are in place. Methods to ensure safe movement to prevent the spread of pests and diseases were also discussed as well as a strategy to conserve coconut diversity in field genebanks.